Analysis and selection of green suppliers using interpretative structural modelling and analytic hierarchy process. (19th February 2008) - Kannan, G.; Haq, A. Noorul; Sasikumar, P.; Arunachalam, Subramaniam
Due to recent changing environmental requirements, increasing attention is given to developing Environmental Management (EM) strategies for the supply chain. A number of organisations are contemplating the integration of environmental practices into their strategic plans. The daily operations are continuously increasing and numerous initiatives have provided incentives for organisations to become more environmental friendly. Some of these regulation-driven programmes are mandatory, but increasingly, numerous voluntary environmental programmes are also introduced by organisations. This study analyses the interaction of criteria that is used to select the green suppliers who address the environmental performance using Interpretive Structural Modelling (ISM) and Analytic Hierarchy Process (AHP). The effectiveness of the ISM and AHP model is illustrated using a automobile company in the southern part of India.